2017
DOI: 10.1088/1361-648x/aa81e6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and heat diffusion of Abrikosov’s vortex-antivortex pairs during an annihilation process

Abstract: Abstract.The manipulation and control of vortex states in superconducting systems are of great interest in view of possible applications, for which mesoscopic materials are good candidates. In this work, we studied the annihilation dynamics and the dissipative aspects of an Abrikosov's vortex-antivortex pair in a mesoscopic superconducting system with a concentric hole. The generalized time-dependent Ginzburg-Landau equations were numerically solved. The main result is the appearance of a phase slip-like line … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 57 publications
(91 reference statements)
0
11
0
2
Order By: Relevance
“…Due to the different geometry and, therefore, different pinning conditions in both partially deoxygenated structures, the number of moving vortices is also different. Heat generated by moving and annihilating bundles of vortices/antivortices in the CC segment can affect the balance between F L and F p [21,22] and stop the movement of vortices. If so, the energy dissipation due to vortex motion will take place in the AB and BC segments of the structure, which are much longer than the CC segment in sample 2.…”
Section: Analysis Of Current-voltage Characteristicsmentioning
confidence: 99%
“…Due to the different geometry and, therefore, different pinning conditions in both partially deoxygenated structures, the number of moving vortices is also different. Heat generated by moving and annihilating bundles of vortices/antivortices in the CC segment can affect the balance between F L and F p [21,22] and stop the movement of vortices. If so, the energy dissipation due to vortex motion will take place in the AB and BC segments of the structure, which are much longer than the CC segment in sample 2.…”
Section: Analysis Of Current-voltage Characteristicsmentioning
confidence: 99%
“…Скачки магнитного потока при поперечной ориентации магнитного поля появляются при понижении температуры в малых полях сначала во втором и четвертом квадрантах, т. е. областях, связанных с проникновением знака. Вследствие этого во втором квадранте образуется граница между областями с вихрями разных знаков с максимальным градиентом потока и при изменении поля на этой границе происходит диссипация энергии и локальное повышение температуры [25], влияющее на образование скачков потока. В целом картина скачков потока при поперечной ориентации магнитного поля соответствует представлению о развитии неустойчивостей при срыве связки вихрей с центров пиннинга в объеме образца.…”
Section: скачки магнитного потока на зависимостях M(h) при поперечной ориентацииunclassified
“…The first term in the equation 4 represents the dissipation due to the induced electrical field E, and the second one is due to the dissipation related to the relaxation of ψ. The dissipated power energy is given in units of 𝐻 𝑐2 2 (0)/[8πκ 2 tGL] As Wtotal diffuses through the system, we couple the thermal diffusion equation to the Ginzburg-Landau ones [12,16]. We take u = 5,79 and γ = 10 (for more details see Ref.…”
Section: Theoretical Formalismmentioning
confidence: 99%
“…Zadorosny et al studied the dynamics of a vortexantivortex pair in several superconducting systems with different areas and with an antidot inserted in the center, they found that in the annihilation process the vortexantivortex pair acquire an elongated format [9]. E. Duarte et al, studied the vortex antivortex annihilation in a mesoscopic superconducting system with a central pinning center, they found a dissipative effect, generating appreciable changes in the order parameter, and the power released in the annihilation of a vortex-antivortex pair is detectable in measurements of the total magnetic moment as a function of time [16]. J. Barba-Ortega et al, investigated the process of annihilation of a vortex-antivortex pair in a superconducting square with a central anti-pinning center.…”
Section: Introductionmentioning
confidence: 99%